Cubic Ca3I3P with ideal charge-two triple point - Yang, Ying (Frontiers in Physics, 2022)
A recent study reported the enhancement of thermoelectric response due to the presence of triple point phonons [Phys. Rev. Mater 2, 114204 (2018)]. Because the topological triple point phonons field is still at its early stage, it is necessary to search for realistic materials with ideal triple point phonons. In this work, we show that cubic Ca3I3P is an excellent material to host the ideal charge-two triple points at high-symmetry points and H. Because the charge-two triple points have a topological charge of |C| = 2, two arc-shaped surface states emanating from the projections of each charge-two triple nodal point can be found in cubic Ca3I3P. It is hoped that the ideal charge-two triple point phonons and the clean phononic arc-shaped surface states in Ca3I3P can be experimentally confirmed shortly.